Potensi Pengembangan Budidaya Rumput Laut Eucheuma Cottonii Di Kawasan Perairan Kelurahan Serangan Kota Denpasar Berbasis Sistem Informasi Geografis - I Wayan Sri Adi Wiryana; Dewa Gede Semara Edi; I Made Kawana (GEMA AGRO, 2018)
Distric of Serangan in Denpasar City Bali Province is an area that has economic, social and ecological value that is very meaningful for the survival of the surrounding community. Considering the potential of seaweed cultivation of Eucheuma cottonii that is not yet optimal in Serangan Village area, it needs to be optimized to measure the potential of seaweed cultivation, to map and determine the location of the potential of seaweed cultivation, to make recommendation of potential sea cultivation location. This research aims (1) To know the potential of seaweed cultivation in Serangan urban area, Denpasar City; (2) To be able to know the area for the development of seaweed cultivation which is potential in Serangan Urban Village Denpasar area. The process of determining the suitability of the area is done by using spatial operation by utilizing GIS application. The method of determining the research point for field observation is done by purposive random sampling, where the determination of research point is done deliberately based on certain considerations. Considerations taken include the current location of cultivation areas, the ideal seaweed cultivation criteria, transportation, safety of researchers, time and cost. All the data collected from the field is analyzed digitally using software QGIS 2.14.0 and Cygwin64 Terminal with interpolasi technique. The result of this research shows that the potential of seaweed cultivation of Eucheuma cottonii in Eucheuma cottonii seaside area is 873,400 sqm. The potential area for the development of seaweed cultivation of Eucheuma cottonii in Serangan Village area of 873,400 sqm if the utilization is 30% of the proper location, then the area that can be used is 262.020 m2, now has been utilized for the cultivation of seaweed Eucheuma cottonii covering 27,488 m2 so that the remaining potential areas to be developed as the location of seaweed cultivation Eucheuma cottonii covering an area of 234,531 m2.